2019
DOI: 10.1101/859553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudomonas aeruginosa is capable of natural transformation in biofilms

Abstract: Natural transformation is a mechanism that enables competent bacteria to acquire naked, exogenous DNA from the environment. It is a key process that facilitates the dissemination of antibiotic resistance and virulence determinants throughout bacterial populations. Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen that produces large quantities of extracellular DNA (eDNA) that is required for biofilm formation. P. aeruginosa has a remarkable level of genome plasticity and diversity that suggests… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…The absence of surface motility of the pilU mutant observed here for A. baumannii phenocopies that of P. aeruginosa (64). Despite this commonality between the two organisms, a recent study by Nolan et al demonstrated that TFP were dispensable for low levels of natural transformation of P. aeruginosa (28), which on February 1, 2021 by guest http://jb.asm.org/ Downloaded from contrasted our findings. Here, we demonstrated that apart from PilU, the pilus components were essential for A. baumannii's natural transformability (Fig.…”
Section: Pilus Mutants Are Impaired In Their Surface Motilitycontrasting
confidence: 87%
“…The absence of surface motility of the pilU mutant observed here for A. baumannii phenocopies that of P. aeruginosa (64). Despite this commonality between the two organisms, a recent study by Nolan et al demonstrated that TFP were dispensable for low levels of natural transformation of P. aeruginosa (28), which on February 1, 2021 by guest http://jb.asm.org/ Downloaded from contrasted our findings. Here, we demonstrated that apart from PilU, the pilus components were essential for A. baumannii's natural transformability (Fig.…”
Section: Pilus Mutants Are Impaired In Their Surface Motilitycontrasting
confidence: 87%
“…In Neisseria gonorrhoeae, genomic DNA is actively secreted through a Type 4 Secretion System by the donor strain delivering a more potent substrate of transformation than DNA released upon autolysis (51,52). In Pseudomonas aeruginosa, DNA release is dependent on a cryptic prophage endolysin that is required from biofilm formation where transformation can also occur (53)(54)(55). We found that DNA concentration in the culture supernatant of A. baumannii strain 40288 was about 2 ng/µL and a potent substrate for transformation, a result consistent with concentration measured in P. aeruginosa strain PAO1 culture (56).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, transformation is defined as the uptake of exogenous DNA from the extracellular milieu. P. aeruginosa was initially considered incapable of natural transformation; however, recent work showed that it could take up environmental DNA, particularly when growing as a biofilm 27,28 . Transformation is harder to trace than conjugation and transduction, making it difficult to quantify its clinical impact.…”
Section: Pathways To P Aeruginosa Antibiotic Resistancementioning
confidence: 99%